JOKOWI’S ECONOMIC POLICY AND ISLAMIC ECONOMICS IN INDONESIA - Muhammad Ramadhan (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
This paper aims to propose substantialisation of the doctrine of Islam in the economic field, explore the ideas of Islamic economics that developed into Islamic economic movements, Islamic banks, and then to the state response seen in national policies in contemporary Indonesia. This paper uses political perspective by looking at the development of increasing degrees of democratization, the information technology revolution, increasing economic growth including rising numbers of the middle class, and the masses of demands of the Indonesian Muslim community in terms of Islamic life, I optimisticly argue that Islamic economics will continue to grow in Indonesia, and it also helped strengthen the national economy and more equitable welfare progress. Keywords: Politics, Islam, Islamic Economics